6‑Alkoxy-5-aryl-3-pyridinecarboxamides, a New Series of Bioavailable Cannabinoid Receptor Type 1 (CB1) Antagonists Including Peripherally Selective Compounds - Röver, Stephan; Andjelkovic, Mirjana; Bénardeau, Agnès; Chaput, Evelyne; Guba, Wolfgang; Hebeisen, Paul; Mohr, Susanne; Nettekoven, Matthias; Obst, Ulrike; Richter, Wolfgang F; Ullmer, Christoph; Waldmeier, Pius; et al. (Journal of medicinal chemistry, 2013)
We identified 6-alkoxy-5-aryl-3-pyridinecarboxamides as potent CB1 receptor antagonists with high selectivity over CB2 receptors. The series was optimized to reduce lipophilicity compared to rimonabant to achieve peripherally active molecules with minimal central effects. Several compounds that showed high plasma exposures in rats were evaluated in vivo to probe the contribution of central vs peripheral CB1 agonism to metabolic improvement. Both rimonabant and 14g, a potent brain penetrant CB1 receptor antagonist, significantly reduced the rate of body weight gain. However, 14h, a molecule with markedly reduced brain exposure, had no significant effect on body weight. PK studies confirmed similarly high exposure of both 14h and 14g in the periphery but 10-fold lower exposure in the brain for 14h. On the basis of these data, which are consistent with reported effects in tissue-specific CB1 receptor KO mice, we conclude that the metabolic benefits of CB1 receptor antagonists are primarily centrally mediated as originally believed.